Securitization : Lessons Learned and the Road Ahead - Segoviano, Miguel (IMF Working Papers; Working Paper ;, 2013)
This paper examines the financial stability implications arising from securitization markets, with one eye on the past and another on the future. The paper begins by deriving a number of 'lessons learned' based on an examination of key industry developments in the years before the crisis. Emphasis is placed on the various ways in which securitization markets dramatically changed shape in the years preceding the crisis, vis-a-vis their earlier (simpler) incarnation. Current impediments to securitization markets are then discussed, including a treatment of various regulatory initiatives, the operational infrastructure of securitization markets, and related official sector intervention. Finally, a broad suite of policy recommendations is presented to address the factors that either contributed to the crisis or may currently be posing obstacles to growth-supportive, sustainable securitization markets. These proposals are guided by the objective of preserving the beneficial features of securitization, while mitigating those that pose a potential risk to financial stability.